Characterization of Sugar Contents and Sucrose Metabolizing Enzymes in Developing Leaves of Hevea brasiliensis - Zhu, Jinheng; Qi, Jiyan; Fang, Yongjun; Xiao, Xiaohu; Li, Jiuhui; Lan, Jixian; Tang, Chaorong (Frontiers in Plant Science, 2018)
Sucrose-metabolizing enzymes in plant leaves have hitherto been investigated mainly in temperate plants, and rarely conducted in tandem with gene expression and sugar analysis. Here, we investigated the sugar content, gene expression, and the activity of sucrose-metabolizing enzymes in the leaves of Hevea brasiliensis, a tropical tree widely cultivated for natural rubber. Sucrose, fructose and glucose were the major sugars detected in Hevea leaves at four developmental stages (I to IV), with starch and quebrachitol as minor saccharides. Fructose and glucose contents increased until stage III, but decreased strongly at stage IV (mature leaves). On the other hand, sucrose increased continuously throughout leaf development. Activities of all sucrose-cleaving enzymes decreased markedly at maturation, consistent with transcript decline for most of their encoding genes. Activity of sucrose phosphate synthase (SPS) was low in spite of its high transcript levels at maturation. Hence, the high sucrose content in mature leaves was not due to increased sucrose-synthesizing activity, but more to the decline in sucrose cleavage. Gene expression and activities of sucrose-metabolizing enzymes in Hevea leaves showed striking differences compared with other plants. Unlike in most other species where vacuolar invertase predominates in sucrose cleavage in developing leaves, cytoplasmic invertase and sucrose synthase (cleavage direction) also featured prominently in Hevea. Whereas SPS is normally responsible for sucrose synthesis in plant leaves, sucrose synthase (synthesis direction) was comparable or higher than that of SPS in Hevea leaves. Mature Hevea leaves had an unusually high sucrose:starch ratio of about 11, the highest reported to date in plants.